1984
DOI: 10.1088/0029-5515/24/7/001
|View full text |Cite
|
Sign up to set email alerts
|

Impurity ion transport studies on the PLT tokamak during neutral-beam injection

Abstract: Radial transport of medium- and high-Z ions during co- and counter-neutral-beam heating in the PLT tokamak is studied, using molybdenum and scandium ions as tracer elements. The time evolution of the radial profiles of several ionization stages of both elements, injected by laser blowoff during the neutral-beam heating, is measured under three significantly different beam-plasma combinations. No noticeable differences in the radial profiles attributable to the beam direction are observed. However, a given inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 20 publications
3
46
1
Order By: Relevance
“…Long wavelength forbidden transitions have been seen in the solar corona [2,3] and in tokamaks [4 -7], and they have been used extensively to probe a variety of properties for both kinds of plasmas. For example, local ion temperatures and bulk plasma velocities can be inferred from the substantial Doppler widths and shifts of these lines [5,6,8]. It is also possible to determine the direction and magnitude of internal magnetic fields from polarization measurements or from Zeeman shifting or broadening of the line profiles [9 -11].…”
mentioning
confidence: 99%
“…Long wavelength forbidden transitions have been seen in the solar corona [2,3] and in tokamaks [4 -7], and they have been used extensively to probe a variety of properties for both kinds of plasmas. For example, local ion temperatures and bulk plasma velocities can be inferred from the substantial Doppler widths and shifts of these lines [5,6,8]. It is also possible to determine the direction and magnitude of internal magnetic fields from polarization measurements or from Zeeman shifting or broadening of the line profiles [9 -11].…”
mentioning
confidence: 99%
“…In the meantime, a number of experiments were performed in ISX-B 11,12 ͑Impurity Studies Experiment B͒ and Princeton Large Torus 13,14 to investigate the effect of NBI direction on central impurity accumulation. These experimental results confirmed the qualitative theoretical prediction that accumulation of impurities in the center of these plasmas was substantially smaller when the magnetic field, beam, and plasma current were parallel than when one was antiparallel to the other two.…”
Section: Introductionmentioning
confidence: 99%
“…then from Equation (13) and (38)(39)(40) we get the relations of the HL and EC values [27] (A1 for C), JT-60 [28] (A2 for C) and JET [29,30,32] (A1, A2, F, H for Ar) tokamaks; (b) reduced velocity profiles n w  (dashed) and n u  (dotted) calculated using Formulas (33).…”
Section: Impurity Equilibrium and Transport Coefficientsmentioning
confidence: 99%
“…In the practice of modeling medium and heavy impurities, that is, with an increase in the rates of ionization-recombination, it was found that the DCM sensitivity to the empirical transport coefficients remains extremely low [7][8][9][10][11][12][13] and just unacceptable for W impurity [14,15].…”
Section: Introductionmentioning
confidence: 99%